Uṣûl al-Fiqh antara Ahl al-Ḥadîth dan Ahl al-Ray - Jeje Abd. Rozaq (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2011)
If there is any notion in which Islam is seriously concerned with more than anything else, it is the notion of freedom of expression. No doubt, Islam has recognized this and has even institutionalized it in the form of what popularly known as ijtihad. Rational exercise is the main trait of this institution, in which a mujtahid would employ a certain method to come up with whatever result he/she has discovered on certain legal issues. In the meantime, the science in which ijtihad is commonly used is called the science of Uṣûl al-Fiqh. This science also provides the guidelines on how intellectual exercise should be carried out. This paper is interested in exploring further this notion of ijtihad within the framework of evolutionist thinking. It assumes that the product of ijtihad, commonly called fiqh, has evolved from being an individual opinion, to become a collective discourse then to a religious dogma. Hence, the paper argues that while ijtihad is a precious gift, it is wrongly misappropriated by certain religious authorities to produce dogmas that can jeopardize the opposing views.